Faktor-Faktor yang Memengaruhi Perilaku Belajar Mahasiswa E-Learning - Enggal Sriwardiningsih (Binus Business Review, 2014)
E-learning becomes one alternative for limited education infrastructure in Indonesia. So technological innovation website is used as one alternative content educational. So that the effectiveness of e-learning system should have constructivism approach when they use this system. This research aims to find variables that could influence e-learning students’ behavior when they use the system. Survey was conducted on e-learning students from Online Binus University and Indonesia Open University (UT).The result of the primary data was processedusing Wrapls 3.0 to process the structure equation model of the frame research. Ten hypotheses were proposed but only some hypotheses were valid. Variables such as motivation, digital literacy, and satisfaction affected directly to the attitude of understanding student learning, while the curriculum material product and interaction e-learning website did not influence the behavior of student e-learning attitude.